Gender-Differences in Reports of Attitudes and Beliefs Concerning Avoiding Alcohol Use and Receipt of Screening by a Healthcare Team Member Among Adolescents with Chronic Medical Conditions - Grill, Sarah. (2017)
Abstract: Adolescent risk-taking is well researched for youth without chronic medical conditions, but very little is known about its effects on youth with chronic medical conditions. Youth with chronic medical conditions who consume alcohol also expose themselves to behaviors and lifestyle factors that may worsen their health. In order to better inform prevention and intervention strategies, we must provide clinicians with a better understanding if gender differences exists in regard to attitudes/beliefs within a chronically ill population, particularly in regards to abstaining from substance use. Moreover, to identify whether there are gender differences in self-reporting of clinical screening. For the purposes of secondary analysis, the study used a census of 260 adolescents. Participants came from one of the following sites: Asthma, Endocrine, Gastroenterology, Rheumatology, or Pulmonary. Measures were used to assess adolescents with chronic illness's attitudes/beliefs about select reasons to abstain from drinking, and their self-report of receiving clinical guidance.; Thesis (M.A.)--Tufts University, 2017.; Submitted to the Dept. of Child Study and Human Development.; Advisor: Dr. Kerri Modry-Mandell.; Committee: Dr. Elissa Weitzman, and Dr. Martha Pott.; Keyword: Psychology.